Isolated ultra-bright attosecond pulses via non-collinear gating. (1st November 2022) - Kennedy, J P; Dromey, B; Yeung, M
Abstract: When light with relativistic intensity is incident on a solid target, bright attosecond pulses of extreme ultraviolet and x-ray radiation can be generated in the reflected beam. Unfortunately, the use of multi-cycle laser pulses results in trains of these attosecond pulses. Here we investigate a non-collinear gating scheme applied to surface high-harmonic generation to allow for the extraction of a single intense attosecond pulse from this train. Using 3D and 2D particle in cell (PIC) simulations we demonstrate that it is possible to angularly isolate a single attosecond pulse from the main driving laser pulse using this interaction geometry with intensities I > 10 20  W cm −2 . This result opens the door to generating bright attosecond pulses from relativistic plasmas without the need to spectrally filter the driving laser pulse.